Feminist political theory : an introduction - Bryson, Valerie (Palgrave Macmillan, 2003)
book provides a wide-ranging history of western feminist thought and a lucid analysis of contemporary debates. It argues that feminism is still relevant today, and that good theory can help us understand why so many problems remain and how progress can be achieved. Rating: